Integrating resilience and nexus approaches in managing flood risk - Raub, Kristin B.; Flynn, Stephen E.; Stepenuck, Kristine F.; Hedderman, Ciaran (Frontiers in Water, 2024)
As climate change has worsened, so too has the risk weather-driven natural disasters pose to critical infrastructure, such as vital food, energy, and water systems. While both the concepts of a food-energywater (FEW) nexus and resilience emphasize the interdependence of complex systems, academic studies have largely neglected a potential synthesis between the two. When applied in tandem, we believe the FEW nexus and resilience can be mutually reinforcing. Nexus approaches can enhance cross-sectoral evaluation and decision making in resilience planning, and resilience-oriented approaches can better situate the FEW nexus within a broader social, ecological, and governance context. From the small body of existing academic literature considering these concepts in tandem, we have identified a promising foundation for relevant future research that targets three key challenges: cooperation, scale, and heterogeneity. Responding to these challenges, in turn, can lead to actions for constructing more resilient infrastructure systems that meet vital human needs in the midst of increasingly frequent floods and other extreme weather events.